Treatment of abdominal wall hernia with suture, or polypropylene, or collagen prosthesis - Garcia,Diego Paim Carvalho (2016)
ABSTRACT PURPOSE: To develop an experimental model for incisional hernias and to compare morphological and functional aspects of hernia repairs by suture, polypropylene mesh and collagen mesh. METHODS: A defect measuring 7cm x 2cm was created in the anterior abdominal of 28 New Zealand male rabbits, divided into four groups (n = 7): (1) control, (2) suture of the anterior sheath of the rectus abdominal muscle, (3) setting of polypropylene mesh, and (4) setting of collagen mesh. On the 90th postoperative day, the animals were examined to verify the presence of incisional hernia. Samples of abdominal wall and scar were collected for histological study. RESULTS: Incisional hernia was identified in 85.7% of the control group, 57.1% of the suture group, 42.9% of the collagen mesh group, and none in the polypropylene mesh group (p = 0.015). Mesh exposure could be identified in 71.4% of the animals in group 3 and in no animal in group 4 (p = 0.021). The polypropylene mesh is effective in the treatment of abdominal wall defects, causing an intense inflammatory reaction. CONCLUSION: The collagen mesh is biocompatible, producing a minimal inflammatory reaction, but fails in the treatment of abdominal wall defects.